2021
DOI: 10.1292/jvms.20-0450
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies virus infection in hunting dogs in Oita, Japan: Report from a prefecture free from Aujeszky’s disease in domestic pigs

Abstract: We isolated two pseudorabies virus (PRV) isolates (designated OT-1 and OT-2) from two hunting dogs exhibiting neurological manifestations after eating the flesh of wild boar hunted in Oita prefecture, Kyushu Island, Japan. The isolates corresponded to a previously reported PRV (MY-1 strain) isolated from a hunting dog in neighboring Miyazaki prefecture, and it clustered into genotype II based on the glycoprotein C sequence. Our results suggest that this common PRV strain may have been maintained in wild boars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Together with the study by Kotnik et al [41], the present study is only the second report of PRV infection in dogs from Slovenia in over 30 years. All cases indicate direct interspecies transmission, similar to previously published results from other countries [10,15,23,24,[26][27][28][29][30][31][32][33]37], confrming the still existing risk of PR and supporting the need for national control programmes in the wild boar population for this disease.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Together with the study by Kotnik et al [41], the present study is only the second report of PRV infection in dogs from Slovenia in over 30 years. All cases indicate direct interspecies transmission, similar to previously published results from other countries [10,15,23,24,[26][27][28][29][30][31][32][33]37], confrming the still existing risk of PR and supporting the need for national control programmes in the wild boar population for this disease.…”
Section: Discussionsupporting
confidence: 86%
“…Two studies published in 2005 and 2014 on serological surveys in Slovenian wild boar showed that PRV circulates with a prevalence of 26% to 45.1% and poses a risk to other susceptible hosts [20,22]. PRV infections in dogs have been previously reported in Europe, the United States, Japan, and China [6,10,[23][24][25][26][27][28][29][30][31][32][33]. In most cases where PRV has been reported in dogs, the dogs became infected directly by ingestion or indirectly by inhalation, or via small wounds from contact with infected pigs [1].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the recent incidents of PRV infecting people, the dog in PRV infection has aroused great concern. PRV is prevalent in dogs, including working and hunting dogs, in the USA [ 17 , 89 , 90 ], Belgium [ 91 ], Italy [ 19 , 75 , 92 ], France [ 93 ], Spain [ 85 , 94 ], Japan [ 95 , 96 ], Austria [ 97 , 98 , 99 ], China [ 18 ], Serbia [ 100 ], Argentina [ 101 ], and Germany [ 74 ], with infection via direct or indirect contact with wild boars and pigs [ 6 , 74 ]. Dogs with PRV infection display neurological signs, anorexia, intense muzzle itch, and respiratory distress [ 1 , 96 ], and usually die within 48 h of clinical symptom onset [ 19 ].…”
Section: Prv Infection In Wild Domestic and Farm Animalsmentioning
confidence: 99%
“…It consists of a unique long region (U L ), a unique short region (U S ), internal repetitive sequences (IRS), and terminal repetitive sequences (TRS) [ 2 ]. The natural host of PRV is pigs, but it can infect most mammals, including cattle, sheep, cats, dogs, mink, and rodents [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. There are significant differences in PRV infection between natural and non-natural hosts [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%